2023
DOI: 10.1029/2022ja031049
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Trends in the Upper Atmosphere Using the Incoherent Scatter Radar Observations Over Arecibo

Abstract: The increasing concentration of anthropogenic greenhouse gases (GHGs) leads to global warming in the lower atmosphere but can cool the upper atmosphere (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
(165 reference statements)
0
1
0
Order By: Relevance
“…However, several studies have indicated that the lower atmospheric gravity waves (GWs) can also influence thermospheric temperatures [Oliver et al, 2013;Lastovica et al, 2006b]. Several other studies related to climatological and long term-term trends have been performed from Arecibo [Brum et al, 2012;Santos et al, 2011;Tepley et al, 2011, Selvaraj et al, 2022. Worth mentioning is the significance of GWs propagation in the weather forecast models that currently use reanalysis data.…”
Section: Figure 2 Arecibo Sodium Resonance Lidar Illustrating High Re...mentioning
confidence: 99%
“…However, several studies have indicated that the lower atmospheric gravity waves (GWs) can also influence thermospheric temperatures [Oliver et al, 2013;Lastovica et al, 2006b]. Several other studies related to climatological and long term-term trends have been performed from Arecibo [Brum et al, 2012;Santos et al, 2011;Tepley et al, 2011, Selvaraj et al, 2022. Worth mentioning is the significance of GWs propagation in the weather forecast models that currently use reanalysis data.…”
Section: Figure 2 Arecibo Sodium Resonance Lidar Illustrating High Re...mentioning
confidence: 99%